Effect of magnetic field on the reconstruction of the defect-impurity state and сathodoluminescence in Si/SiO₂ structure - Steblenko, L.P.; Koplak, O.V.; Syvorotka, I.I.; Kravchenko, V.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
Impurity states in Si/SiO₂ structure have been studied using cathodoluminescence (CL). It has been found that intrinsic structure defects in Si/SiO2 are sensitive to the action of magnetic field, which can be revealed due to changes in Si/SiO₂ optical properties. The most sensitive to magnetic field (about 35 per cent) is the intensity of the 1.9 eV CL band attributed to non-bridge oxygen atoms.